The Pleomorphic Dermal Sarcoma: Its management, follow-up and the need for more guidance - Robert L Devine; Alice Cameron; Adam M Holden; Ahmed Basiouni; Serryth D Colbert (Elsevier, 2021)
Pleomorphic Dermal Sarcoma (PDS) is a rare neoplasia that shares many molecular, histological and clinical commonalities with the atypical fibroxanthoma (AFX), and may even be considered on the same pathological scale. Despite these shared commonalities, PDS has been shown to exhibit aggressive local invasion and distant metastasis. This case report highlights an 80-year-old gentleman who presented with a bleeding nodule on the right scalp, clinically consistent with squamous cell carcinoma, amelanotic melanoma and AFX. Excision of the lesion and subsequent histological and immunohistochemical evaluation confirmed the presence of a PDS. We aim to present this rare tumour to the reader by discussing the clinical presentation, histological and immunohistochemical presentation and reconfirm the importance of the PDS. To our knowledge, there are no currently agreed guidelines on standardised management and follow-up of these cases. By producing this case report we are hoping to add support and to encourage national and international surgical oncological societies to develop a consensus management approach to PDS.